Preparation of an Anodic Alumina-Supported Ni Catalyst and Development of a Catalytic Plate Reformer for the Steam Reforming of Methane - Shan Dong; Yi Lin; Jiajun Hu; Chenglin Gu; Leilin Ding; Xinjian Zhang; Shi Jiang; Yu Guo (Energies, 2023)
A plate-type Al/Fe–Cr alloy/Al-clad substrate was used to prepare a sandwich-structured plate-type anodic alumina catalyst by anodization, post-modification treatment, and metal loading. The as-prepared plate-type catalyst was utilized in the design of a catalytic plate reactor for a methane steam reforming reaction, and a 3D model was developed to simulate the performance of tube-type and box-type reformers. The experimental results of the preparation of the clad materials showed that the hydrothermal treatment and subsequent high-temperature calcination transformed the amorphous skeletal alumina in the conventional anodic alumina layer into γ-alumina, and significantly increased its specific surface area. Simulation results showed that the temperature difference between the channel wall and the center of the gas phase of the thin-walled catalyst was only 30% of that of the particulate catalyst, indicating the potential advantages of the catalytic plate reactor in terms of heat transfer and energy saving. When the length-to-diameter ratio (or length-to-width ratio) of the reaction channel is small and the channel height is large, insufficient transverse mass transfer and backmixing are two major factors affecting reformer performance. For the tube-type channels, a length-to-diameter ratio of 10~35, and a diameter of 5~20 represent favorable choices. In contrast, for the box-type channel, the length-to-width ratio and the height should be set to 2~4 and 2~5 mm, respectively. Additionally, for box-type channels, the number of gas inlet ports has a significant effect on the reformer performance, and the distribution state provided by two inlet ports is close to the ideal distribution state.